A SCIENTOMETRIC ANALYSIS OF ACADEMIC PERFORMANCE DEVELOPMENT: R BIBLIOSHINY - Septian Cahya Azhari; Siti Fadjarajani; Muhamad ferdi Firmansyah; Tita Yuniarti (LPPM Universitas Negeri Jakarta, 2023)
The development of research in the field of education experiences exponential growth every year. This study aims to analyze the development of research on academic performance from 2010-2022. A total of 1906 articles indexed by the PubMed database were analyzed with a scientometric qualitative approach with bibliometric R bibliophily and VosViewer R tools. The results showed a significant development of research on the object of study of academic performance, especially in 2020-2022. From the analysis of several articles, this development was primarily influenced by the covid-19 pandemic. Some authors are categorized as productive writers on this theme, in most of them are from China. The potential for future research by looking at the research keywords of bibliometric analysis results in cluster 1, such as academic functioning, school performance, educational attainment, socioeconomic status, sleep duration, and parental education, is about increasing